Positioning through address practice in Finland-Swedish and Sweden-Swedish service encounters - Catrin Norrby; Camilla Wide; Jenny Nilsson; Jan Lindström (John Benjamins Publishing Company, 2022)
This chapter investigates social positioning through the use (or non-use) of address pronouns in Finland-Swedish and Sweden-Swedish service encounters recorded at theatre and event booking venues in Finland and Sweden. The results demonstrate some compelling variation in address practices which can be attributed to participant roles (customer or staff), national variety (Finland-Swedish or Sweden-Swedish), age (younger or older speaker and addressee) and situational circumstances, such as type of venue and type of transaction, as well as micro-situational aspects which occur during the course of the interaction (complications, problems or topics treated as sensitive). The study highlights that different forms of address cannot be associated a priori with a certain level of formality, but should be interpreted in their micro and macro contexts in order to understand existing cultural norms for appropriate address.
Positioning the Self and Others. Linguistic perspective